Women artists - Frigeri, Flavia (Art essentials., 2019)
"Focusing on fifty diverse women artists, from Lavinia Fontana and Artemisia Gentileschi through Judy Chicago, Ana Mendieta and the Guerrilla Girls to Barbara Kruger, Cindy Sherman and Louise Bourgeois, this book equips the reader with a general understanding of the history of art by women, as well as an appreciation of its most outstanding figures. Traditionally women have been among art's favoured objects of representation, while their contributions as art producers have been subordinated to those of men. This book documents women artists in context to offer readers an accessible but rich understanding of key female artists from the Baroque to the present day."--